Review of the biology and exploitation of striped dolphins in Japan - Kasuya, Tosnio (J. Cetacean Res. Manage., 1999)
The biology, distribution, abundance and exploitation of striped dolphins off Japan are reviewed in an attempt to collate the available information required for a better understanding of the status of populations exploited by Japanese fisheries. Striped dolphins are found in summer in three geographical aggregations in the Pacific waters off Japan, between 20° and 42°N. Occurrence is seasonal in the northern part of the range. They are uncommon in the Sea of Japan, East China Sea and Ryukyuan waters. School structure is believed to be fluid ‘Weaned juveniles usually leave their natal schools to aggregate with individuals of similar age. Adults move between schools dependi on sex and reproductive stanus. They have beon harvested along the Japanese coast since at least the 19th century. An annual catch of t0 21,000 continued from the end of World War II to the end of 1950s. This has been followed by a gradual decline in catches despite demand for dolphin meat. Changes in life history parameters such as female age at sexual maturity and perhaps in female reproductive eycles have occurred over time. Japanese multispecies dolphin fisheries now receive an annual quota of 725 striped dolphins. Fragmented information on morphology, life history, pollutant levels and genetics suggests that the striped dolphins taken by Japanese fisheries are from ‘more than one population, with varying proportions among fisheries and perhaps over time. Further study is needed to clarify population structure, immigration among populations, site fidelity and the function of dolphin ‘schools’.